2011
DOI: 10.1016/j.ijadhadh.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A new source of natural adhesive: Acacia mangium bark extracts co-polymerized with phenol-formaldehyde (PF) for bonding Mempisang (Annonaceae spp.) veneers

Abstract: Acacia mangium is a fast-growing dicotyledonous tree species and has become the dominating plantation in Malaysia. It was grown particularly as a raw material for veneer, pulp, and paper industries. The chemical properties test in this study showed that the A. mangium tree bark contains higher extractive content as compared to the wood portion (sapwood). Tannin extracts from A. mangium tree bark were found to be rich in phenolic compounds and had the potential to replace conventional phenol-formaldehyde (PF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 10 publications
4
26
0
3
Order By: Relevance
“…The low molecular weight phenolic (LmwPF) resin, with desired solid content (20%, 30%, 40%) that was prepared according to Hoong et al [6][7][8], which is by reacting phenol and formaldehyde in an alkaline condition were used as the filling agent in the pretreatment of OPS veneer. The resin cooking procedure were as the normal PF resin cooking for plywood with, minor modified where the methylolation period was maintained less than 4 h. The specifications of the resin used in this study were shown in Table 1.…”
Section: Preparation Of Lmwpf Resinmentioning
confidence: 99%
“…The low molecular weight phenolic (LmwPF) resin, with desired solid content (20%, 30%, 40%) that was prepared according to Hoong et al [6][7][8], which is by reacting phenol and formaldehyde in an alkaline condition were used as the filling agent in the pretreatment of OPS veneer. The resin cooking procedure were as the normal PF resin cooking for plywood with, minor modified where the methylolation period was maintained less than 4 h. The specifications of the resin used in this study were shown in Table 1.…”
Section: Preparation Of Lmwpf Resinmentioning
confidence: 99%
“…Addition of tannins extracted from chestnut wood into PF resins shortened the pressing times by 33% without deteriorating the gluing quality of plywood (Kulvik, 1977). Hoong et al (2011) extracted tannin from Acacia mangium tree bark in water at 75 • C, then prepared a tannin solution of 40% solid content, and formulated the tannin solution with a commercial PF resole at the weight ratio of 50:50, 70:30 and 90:10, to which wheat flour with 3% paraformaldehyde was added as the harder. Results showed the formulated tannin-paraformaldehyde-PF (90 parts tannin, 10 parts commercial PF, 3% paraformaldehyde) adhesive contributed to shear strength meeting the requirement for European norms EN 314-1 and EN 314-2:1993 with respect to dry tests, cold water and even boiling tests on the bonded plywood.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are considered to be environmentally friendly due to the fact that they incorporate lignocellulosic biomass, which is a renewable resource, as a raw material. Usually, synthetic resin adhesives derived from fossil resources are used in wood-based materials to obtain satisfactory bond performance (Yang et al 2006;Mansouri et al 2007;Krug 2010;Hoong et al 2011). However, as the shortage of fossil resources and the deterioration of global environment have been serious problems, it is necessary to develop renewable resources instead of fossil resources.…”
Section: Introductionmentioning
confidence: 99%